Role of microglia in the pathogenesis of multiple sclerosis and links to immunomodulatory therapy - Valiukevičius, P.; Liutkevičienė, R.; Balnytė, R. (Neurologijos seminarai, 2023)
Multiple sclerosis is a chronic autoimmune disease of the central nervous system. Multiple sclerosis causes demyelination, impaired nervous system function, and eventually neurodegeneration. Microglia are cells of the central nervous system that develop from yolk sac macrophages during embryogenesis. These cells perform important functions in the development of the central nervous system and the retina, in the formation of synapses, protect against pathogens, and are involved in the removal of damaged structures. In response to environmental factors, microglia can acquire an inflammatory or anti-inflammatory phenotype. Microglia also play an important role in the pathogenesis of multiple sclerosis, and these cells are thought to be involved in both demyelination and remyelination processes. Microglial cells phagocytose harmful myelin remnants, promote remyelination, and control the proper response of peripheral immune cells, but disruption of these functions can lead to demyelination and neurodegeneration. Many of the disease-modifying drugs used to treat multiple sclerosis also affect microglial cells and inhibit their inflammatory response. Currently, new drugs are being researched that could be used to treat multiple sclerosis promoting the transition of microglia to an anti-inflammatory phenotype. The latest advanced cell therapy drugs have a broader spectrum of action – they inhibit inflammation, promote angiogenesis, perform trophic function, and inhibit oxidative damage.